Dampak Teknologi Terhadap Ruang Lingkup Pembelajaran SKI dalam Membangun Kesadaran Sejarah dan Identitas Budaya Generasi Z - Meliny Meliny; Noorazmah Hidayati (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
Generation Z, known as the internet generation, has unique characteristics that influence the way they learn. Technology-based learning, such as the use of animated videos and interactive applications, can increase students' interest and understanding of complex SKI material. This article discusses the impact of technology on the scope of SKI learning in building historical awareness and cultural identity for Generation Z. This research method uses library research, namely searching for research sources by collecting several pieces of literature sourced from journals, books and other sources. The results of this research show that the rapid development of technology is currently having a significant impact on the field of education, including learning the History of Islamic Culture (SKI).